Coconut Husk And Eggshell Liquid Organic Feltilizer Effect On Lettuce Growth And Calcium Levels - Khotimah, Widya Husnul; Asngad, Aminah (Universitas Muhammadiyah Surakarta, 2023)
Coconut husks and eggshells are common wastes found in society, but they are used less, so they often accumulate. Liquid organic fertilizer (POC) is a solution formed from plant residues, agro-industrial waste, animal dirt, and human dirt that has a content of more than one element. This research aims to find out the effectiveness of the supply of liquid organic fertilizer from coconut seeds and egg shells against the increase in calcium (Ca) and the growth of lettuce plants (Lactuca sativa l). The research was conducted at FKIP Muhammadiyah University of Surakarta’s Green House Education Biology from January–April 2023. The study used the complete random design (RAL) method of 3 repetitions and two factors: the POC administration concentration used P0 (POC 0 ml), P1 (POC 100 mL), and P2 (POC 150 mL), and the time interval for POC W1 (once every 3 days), and W2 (once every 5 days). The results of the research showed that the highest growth and increase in calcium being seen with the treatmentof P2W2 (150 ml POC and once every 5 days).